An Observational Registry of Carotid Endarterectomy and Carotid Artery Stenting in Brazil: Study Protocol - Joviliano, Edwaldo Edner; Yoshida, Winston Bonetti [UNESP]; Sobreira, Marcone Lima [UNESP]; Moura, Regina [UNESP]; Guillaumon, Ana Terezinha; De Oliveira Raymundo, Selma Regina; Miquelin, Daniel Gustavo; Hafner, Ludvig; Almeida, Marcelo Jose (Jmir Publications, Inc, 2016)
Background: Carotid artery stenting (CAS) and carotid endarterectomy (CEA) are alternative strategies for stroke prevention in patients with atherosclerotic carotid disease. CEA has been considered the first-line treatment for carotid stenosis worldwide, and the safety and efficacy of CAS compared to CEA remains in question. Objective: The purpose of this study is to compare the practice and outcomes of CAS and CEA in a real-world setting within public university hospitals in Brazil. Methods: This study will be a prospective 5-year analysis of treatment for atherosclerotic carotid stenosis with CEA and CAS performed at 5 centers affiliated with the Vascular Study Group at public university hospitals in Brazil. The indications for the procedures will be determined by each surgeon's individual discretion, in accordance with preoperative risk evaluation. The primary outcome measures will be (1) any in-hospital stroke or death, and (2) any per-procedural stroke, death, or myocardial infarction (MI). Patients undergoing CEA in conjunction with cardiac surgery will be excluded from the study. Multivariate logistic regression will be performed to identify predictors of stroke or death in patients undergoing CEA and CAS. All tests of significance will be performed at the .05 level. This study was approved by the Committee of Ethics in Research at the University Hospital of Ribeirao Preto Medical School, and in all other participating institutions linked to National Research System and National Board of Health in Brazil (Process 15695/2011). Results: This study is currently in the recruitment phase, and the final patient is expected to be enrolled by the end of 2018. We hope to recruit approximately 800 patients to the study. Analyses will focus on primary end points for patients that are allocated to each treatment group. During the per-procedural period, the occurrence of the primary end point components (stroke, MI, or death) for CAS and CEA will be analyzed for symptomatic or asymptomatic subjects. Conclusions: The analyses of the primary endpoints (and all others variables of the study) are expected to be published in 2019 in a peer reviewed journal, and results will be presented at scientific meetings, with summary results published online. This study will obtain new data related to the quality of treatment for carotid disease in Brazil at the primary training centers of future vascular surgeons, but the initial data that will be obtained and published (with the outcomes and complications) are restricted to the first 30 days postprocedure. This time restriction limits the comparison of the results that relate to the main goal of treatment, which is to decrease the risk of stroke over 5 years. The purpose of the study group is to continue the monitoring of patient records, and evaluate the follow-up data in the 5 years following the initial evaluation. This study protocol will contribute very significantly to improving the care of patients with carotid disease, in addition to qualifying the level of assistance provided in public university hospitals in the state of Sao Paulo, Brazil.
Keywords: carotid artery diseases; carotid endarterectomy; carotid stenosis; carotid stenting; medical record linkage